ANALISIS NARATIF PENGAJIAN TAFSIR JALALAIN KHR. ACH. AZAIM IBRAHIMY DI CHANNEL YOUTUBE S3TV - Soliha Rohman; Yohandi, Yohandi (Fakultas Dakwah Universitas Ibrahimy, 2025)
This study is to describe the narrative structure in the Tafsir Jalalain study by KHR. Ach. Azaim Ibrahimy on the S3TV Youtube channel. In the past, humans searched for information through newspapers, television, radio and magazines, but now it can be done using social media as a medium of communication and information. Preaching through social media can facilitate the message to be conveyed more quickly received by all levels of society and is not limited by distance and time. Youtube is currently one of the media for delivering da'wah. The messages of da'wah delivered by da'i are increasingly popular with the public, especially those who often access the internet. S3TV is the official youtube channel of the Salafiyah Syafi'iyah Islamic Boarding School which has been used as a da'wah medium since January 18, 2018 until now. The S3TV Vol. 7 No. 1 Januari 2025 183 | J U R N A L K O M U N I K A S I D A N K O N S E L I N G I S L A M Youtube channel has 73.5 thousand subscribers, with 6,065 videos, and has been watched 9,027,890 times, one of which is in the